Human error identification and risk prioritization in overhead crane operations using HTA, SHERPA and fuzzy VIKOR method. Issue 20 (15th November 2015) - Mandal, Saptarshi; Singh, Karmveer; Behera, R.K.; Sahu, S.K.; Raj, Navneet; Maiti, J.
Highlights: This work develops a methodology for human error identification and prioritization. HTA and SHERPA have been used for human error analysis. Experts' linguistic input w.r.t risk parameters is modeled using fuzzy logic. Fuzzy VIKOR method has been used for risk prioritisation purpose. This work will help in safety critical resource allocation strategy development. Abstract: Human error identification and subsequent prioritization are the foremost tasks involved in HRA. In this study a methodology is developed for performing these tasks with an application to overhead crane operations. The application of the present methodology will help to understand how the risk associated with the human errors propagates through different hierarchy levels. The methodology provides a framework for quantifying the risk of different human errors using the experts' subjective opinions only. The incorporation of fuzzy VIKOR technique enables us develop a ranking mechanism for the failure modes where the individual constituent components are non-commensurable in nature. The developed ranking mechanism helps the decision makers in optimal allocation of safety critical resources, used for risk mitigation purposes.